Avaliação de um pulverizador e volume ultra baixo e de adjuvantes em caldas fitossanitárias na cultura dos citros - Decaro Junior, Sergio Tadeu [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Sprays in citrus orchards are performed by means of excess of applied volume, which implies in high operational cost and decrease of the competitiveness in this sector. The present work evaluated reductions on the application volume in citrus, employing a conventional sprayer and an ultra low volume sprayer, by means of jets setting and nozzles change. The nozzles named effervescent of the ultra low volume sprayer were assessed on the droplet spectra produced with spraying liquids containing adjuvants in different concentrations, comparing to the pattern water. All the spraying liquids utilized at the field application and at the nozzles evaluation, along with fungicide liquids with mineral oil and manganese sulphate concentrations, were assessed according to different variables. They were surface tension, viscosity, density, pH, conductivity, stability, sprayed droplets diameter, contact angle of droplets and liquid retention on citrus leaves, aiming to identify similarity among the spraying liquids and correlations among variables. From the results, the volume 630 L ha-1, with the conventional sprayer, and the volume 160 L ha-1, with the ultra low volume sprayer, may be adopted for the control of pathogens, on citrus plants, with similar coverage and higher fungicide volume deposited on the leaves in comparison with the volume of 1,200 L ha-1 conventionally practiced. The effervescent nozzle produces very fine droplets, in such a way the use of mineral oil in concentrations higher than 11%, as well as the adjuvant heptamethyltrisiloxane, on recommended dosage, reduce the risk of droplets from drift, whilst the adjuvant phosphatidylcholine favors the production of more fine and uniform droplets. The choice of determined adjuvant must presuppose effect in several variables of the spraying liquid, opting for products with a more pronounced effect on the variable of agronomic interest. The higher was the viscosity, the higher was the ...

As pulverizações na cultura dos citros são realizadas por meio de excesso no volume de calda aplicado, o que implica em alto custo operacional e perda na competitividade do setor. O presente trabalho avaliou reduções no volume de aplicação em citros, usando-se um pulverizador convencional e um pulverizador de volume ultra baixo, por meio de direcionamento de jatos e troca de bicos. Os bocais denominados efervescentes do pulverizador de volume ultra baixo foram avaliados quanto ao espectro de gotas pulverizadas mediante a utilização de caldas contendo adjuvantes em diferentes concentrações, comparado ao padrão água. Todas as caldas utilizadas na aplicação a campo e na avaliação do bocal, juntamente com caldas fungicidas contendo variações na concentração de óleo mineral e sulfato de manganês, foram avaliadas segundo diferentes variáveis. Foram elas a tensão superficial, viscosidade, densidade, pH, condutividade, estabilidade, diâmetro das gotas pulverizadas, ângulo de contato de gotas e retenção de calda em folhas de citros, visando a identificar similaridades entre caldas e correlações entre variáveis. De acordo com os resultados, o volume de 630 L ha-1, no pulverizador convencional, e o volume de 160 L ha-1, com o pulverizador de volume ultra baixo, podem ser adotados para o controle de patógenos, em plantas de citros, com igual cobertura e maior volume de fungicida depositado nas folhas em relação ao volume de 1.200 L ha-1 convencionalmente praticado. O bocal efervescente produz gotas muito finas, de modo que o uso do adjuvante óleo mineral em concentração maior que 11%, bem como o adjuvante heptametiltrisiloxano, na dose recomendada pela bula, reduzem o risco de deriva das gotas, enquanto o adjuvante fosfatidilcoline favorece a produção de gotas mais finas e uniformes. A escolha de determinado adjuvante deve pressupor efeito em várias variáveis na calda, optando-se por produtos que tenham efeito...
Keywords: Cítricos; Pulverização; Máquinas agrícolas; Oleos minerais; Defensivos vegetais - Tecnologia de aplicação; Spraying